Experimental studies and computational modeling on cytochrome c reduction by quercetin: The role of oxidability and binding affinity - Zazeri, Gabriel [UNESP]; Povinelli, Ana Paula Ribeiro [UNESP]; Pavan, Nathalia M. [UNESP]; de Carvalho, Daniella Romano; Cardoso, Carmen Lúcia; Ximenes, Valdecir Farias [UNESP] (Elsevier, 2021)
Quercetin is a potent reducing agent of cytochrome C (Cyt c). Cyt c plays a fundamental role in the intrinsic apoptotic pathway, and there is evidence of the quercetin's role in this cellular event, which is involved in several biological effects of this phytochemical. In this work, we questioned ourselves if something special in quercetin could explain its high reactivity with Cyt c. The reducing potency of quercetin was compared with other antioxidants. Among them, gallic acid was more effective than quercetin as a reducer of the 2,2-diphenyl-1-picrylhydrazyl free-radical and less efficient in the 2,4,6-tri(2-pyridyl)-S-triazine-complexed ferric ion reduction assay. Regarding Cyt c reduction, which is also related to ferric reduction, quercetin was significantly more potent than gallic acid. These findings were explained by molecular docking and dynamics simulations, which indicated that quercetin has more privileged access to the protoporphyrin prosthetic group and more negative binding free energy (-46.4 ± 2.0) than gallic acid (-13.9 ± 6.8) kJ/mol. Over the 35 ns of molecular dynamics, the reduced form of quercetin remained in the binding pocket, while the oxidized form dissociated from the protein after 20 ns. The oxidation of quercetin had as an outcome the formation of a heterodimer. In the reaction course, the transient quercetin free-radical was able to oxidize glutathione. This result is an in vitro demonstration of quercetin's pro-oxidant features, an effect that has been reported in the cellular medium. In conclusion, the reaction between Cyt c and quercetin is related to its reduction potential and favorable protein-ligand interaction. This reaction can play a role in apoptosis triggered by quercetin.
Keywords: Cytochrome C; Molecular dynamics; Pro-oxidant activity; Quercetin; Quercetin dimer